The Influence of Preoperative Mood and Treatment Expectations on Early Postsurgical Acute Pain After a Total Knee Replacement - Stuhlreyer, Julia; Klinger, Regine (Frontiers in Psychiatry, 2022)
Background Reducing postoperative pain immediately after surgery is crucial because severe postoperative pain reduces quality of life and increases the likelihood that patients develop chronic pain. Even though postoperative pain has been widely studied and there are national guidelines for pain management, the postoperative course is differently from one patient to the next. Different postoperative courses could be explained by factors related to the treatment context and the patients. Preoperative emotional states and treatment expectations are significant predictors of postoperative pain. However, the interaction between emotional states and preoperative treatment expectations and their effect on postoperative pain have not yet been studied. The aim of our study was to identify the interaction between emotional states, treatment expectation and early postsurgical acute pain. Methods In this prospective clinical trial, we enrolled patients who had received a TKR at a German hospital between October 2015 and March 2019. Patients rated their preoperative pain on a numeric rating scale (NRS) 0–10 (0=no pain and 10=worst pain imaginable), their emotional states preoperatively on the Pain and State of Health Inventory (PHI), their preoperative treatment expectations on the Stanford Expectation of Treatment Scale (SETS), and their postoperative level of pain on a NRS 0-10. Findings The questionnaires were completed by 122 patients (57% female). Emotional states predict negative treatment expectation F(6, 108)=8.32, p<0.001, with an excellent goodness-of-fit, R²=0.31. Furthermore, a mediator analysis revealed that the indirect effects and therefore relationship between the emotional states sad (ab=0.06, 95% CI[0.01, 0.14]), anxious (ab=0.13, 95% CI[0.04, 0.22]), and irritable (ab=0.09, 95% CI[0.03, 0.17]) and postoperative pain is fully mediated by negative treatment expectations. Whereas the emotional states tired (ab=0.09, 95% CI[0.03, 0.17]), dizzy/numb (ab=0.07, 95% CI[0.01, 0.20]), weak (ab=0.08, 95% CI[0.03, 0.16] are partially mediated by negative treatment expectations Conclusion The relationship between emotional states and postoperative pain is mediated by negative treatment expectations. Therefore, innovative treatment strategies to reduce postoperative pain should focus on eliminating negative treatment expectation through establishing a differentiated preoperative expectation management program that also focuses on emotional states.